1981
DOI: 10.1093/nar/9.22.6167
|View full text |Cite
|
Sign up to set email alerts
|

Secondary structure model for 23S ribosomal RNA

Abstract: A secondary structure model for 23S ribosomal RNA has been constructed on the basis of comparative sequence data, including the complete sequences from E. coli. Bacillus stearothermophilis, human and mouse mitochondria and several partial sequences. The model has been tested extensively with single strand-specific chemical and enzymatic probes. Long range base-paired interactions organize the molecule into six major structural domains containing over 100 individual helices in all. Regions containing the sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
257
1
3

Year Published

1985
1985
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(270 citation statements)
references
References 55 publications
7
257
1
3
Order By: Relevance
“…Phylogenetic analysis is the most accurate method for RNA secondary structure prediction. Some structures determined by this method include tRNAs (24), ribosomal RNAs (25)(26)(27), group I and group II introns (28,29), RNAs from small nuclear ribonucleoproteins (30), hammerhead catalytic RNA (31), and RNase P RNAs (32). Further studies have confirmed these structures.…”
Section: Discussionmentioning
confidence: 91%
“…Phylogenetic analysis is the most accurate method for RNA secondary structure prediction. Some structures determined by this method include tRNAs (24), ribosomal RNAs (25)(26)(27), group I and group II introns (28,29), RNAs from small nuclear ribonucleoproteins (30), hammerhead catalytic RNA (31), and RNase P RNAs (32). Further studies have confirmed these structures.…”
Section: Discussionmentioning
confidence: 91%
“…Shaded sequences representing mature RNAs were taken from earlier models (4,28,37,38) and the arrows represent cleavages which produce the mature ribosomal RNAs. The insert (upper right) is an estimate for the secondary structure in the ITS 2 equivalent region of Escherichia coli based on the 238…”
Section: Structure and Evolution Of The 23-45-5s Rrna Precursor Sequmentioning
confidence: 99%
“…NINA models from the laboratories of Brimacombe (37) and Noller (38). regions evolved, at least in part, through gene duplication events probably the result of unequal crossing over.…”
Section: Structure and Evolution Of The 23-45-5s Rrna Precursor Sequmentioning
confidence: 99%
“…We show that the gene carries a transcribed spacer of approximately 147 bp which results in the production of fragmented 23S rRNA, and we demonstrate that this is a common phenomenon in C. coli and C. jejuni because many strains carry transcribed spacers of this approximate length or shorter ones and also produce fragmented 23S rRNAs. In addition, we report on the phylogenetic position of the genus Campylobacter, based on the presence of phylogenetic signatures at positions 270 and 1850 (E. coli numbering [36]) of the Campylobacter 23S rRNA, and on a phylogenetic analysis which was performed by using this C. coli 23S rRNA, a C. jejuni 23S rRNA sequence (GenBank accession number Z29326), and 53 other available complete (eu)bacterial 23S rRNA sequences. …”
mentioning
confidence: 99%